PENGARUH TOUGHT STOPING TERHADAP TINGKAT KECEMASAN REMAJA YANG MENGALAMI BULLYING DI PESANTREN - Yani, Athi' Linda (The Indonesian Journal of Health Science, 2017)
Bullying can be physical, verbal, and emotional form. Bullying is a repeatedly of violent behavior,  this  occurs  in  many  times  and  had  psychological  and  physical  coercion occurs against bullying victims. Bullying in Indonesia is found in many schools both formal and non formal. According to previous research, cases of bullying is around 61 - 73% in the form of violence, extortion, threatening and taking goods, the rest is a case of bullying in other forms such as cyber bullying. The aim of this study were: 1) To determined the level of anxiety among teenagers who experienced victims of bullying before being given tought stoping, 2) to assess the level of anxiety among teenagers who experienced victims of bullying after being given tought stoping and 3) to analyze the level of anxiety before and after giving therapy of tought stoping. The methodology in this research used pre design post test design, and the data were analized by using T- test. The population in this study were adolescents who live in pesantren. The sample in this study 30 participants with inclusion criteria. The inclusion criteria are adolescents who living in pesantren and who experienced bullying. sampling technic used purposive sampling technique. The results of this study found that there is the influence of tought stoping to Anxiety Level Among Teenagers after giving tought stoping. It mean that there is a significant decrease from the level of high anxious than can be decreased to moderate level. The ability to control positive thoughts is strongly recommended so this will make easy to prevent to getting bullying.Keywords: Thougt Stoping, Anxiety, Teenager, Pesantren